2019
DOI: 10.26717/bjstr.2019.22.003700
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Treatment Seeking Behavior for Malaria in May-Aynee Administration, Eritrea

Abstract: Objective: Malaria is an entirely preventable and treatable disease. However, due to lack of adherence to the preventive measures and delay in early treatment, it has become one of the leading public health problems. The general objective was to assess knowledge, attitude and early treatment seeking behavior about malaria among the communities residing in May-Aynee administration, Eritrea. Method:We conducted a community based cross sectional study. Using systematic random sampling proportional to the size of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…[27] The study reports that among those with undifferentiated fever, less than one-third get their blood tests done for malaria despite the fact that most of them seek care [28] Findings of this study reveal high cost of services and long distances to health facilities were the challenges affecting treatment seeking behavior as many they sought to delay at health facility for somedays, whereby 73% they did not prefer to go at health facility till the condition seem to persisted. Compared to studies done Eritrea showed that cost is often a barrier to seeking health services especially among the poor [22] Limitation of the study Inadequate fund to carry out this study, Language barrier as most of people they speak in Sukuma language, the study requires a larger number of participants hence was consumed time in data collection and analysis.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…[27] The study reports that among those with undifferentiated fever, less than one-third get their blood tests done for malaria despite the fact that most of them seek care [28] Findings of this study reveal high cost of services and long distances to health facilities were the challenges affecting treatment seeking behavior as many they sought to delay at health facility for somedays, whereby 73% they did not prefer to go at health facility till the condition seem to persisted. Compared to studies done Eritrea showed that cost is often a barrier to seeking health services especially among the poor [22] Limitation of the study Inadequate fund to carry out this study, Language barrier as most of people they speak in Sukuma language, the study requires a larger number of participants hence was consumed time in data collection and analysis.…”
Section: Discussionmentioning
confidence: 91%
“…Similar findings were reported in Ethiopia, Eritrea and Myanmar. [22,23,24] The health facility where people prefer to seek for treatments after the onset of illness, study…”
Section: Discussionmentioning
confidence: 99%
“…[27] The study reports that among those with undifferentiated fever, less than one-third get their blood tests done for malaria despite the fact that most of them seek care [28] Findings of this study reveal high cost of services and long distances to health facilities were the challenges affecting treatment seeking behavior as many they sought to delay at health facility for somedays, whereby 73% they did not prefer to go at health facility till the condition seem to persisted. Compared to studies done Eritrea showed that cost is often a barrier to seeking health services especially among the poor [22] Limitation of study Inadequate fund to carry out this study, Language barrier as most of people they speak in Sukuma language, the study requires a larger number of participants hence was consumed time in data collection and analysis.…”
Section: Discussionmentioning
confidence: 93%
“…Similar ndings were reported in Ethiopia, Eritrea and Myanmar. [22,23,24] The health facility where people prefer to seek for treatments after the onset of illness, study show that majority of people they tend to seek treatment earlier at pharmacy (drug shop) to buy medicine for selftreatment than other places like hospital or health center and laboratory. [24] The number of people who seek for treatment at pharmacy and local drug shops were higher compared to those who seeking for treatments in other health facilities.…”
Section: Discussionmentioning
confidence: 99%